2012
DOI: 10.1074/jbc.m112.378554
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Currents Are Enhanced by α2δ-1 Lacking Its Membrane Anchor

Abstract: Background: We examined the role of membrane anchoring of voltage-gated calcium channel α2δ subunits.Results: We used a truncated α2δ-1 construct (α2δ-1ΔC-term), which still increases CaV2.1/β1b currents, despite being mainly secreted.Conclusion: The effect of α2δ-1ΔC-term on calcium currents does not involve secretion and subsequent re-binding to the plasma membrane.Significance: C-terminal membrane anchoring of α2δ is not essential for calcium current enhancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
74
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(82 citation statements)
references
References 41 publications
8
74
0
Order By: Relevance
“…We therefore examined the cell-surface expression of α 2 δ-1-HA, and the effect of Ca V 2.2 coexpression on this, to gain insight into the interaction site of the auxiliary subunits, with the aim of determining whether they remained associated as judged by colocalization at the cell surface. We used α 2 δ-1-HA for these studies, as we have shown previously that it supports calcium channel currents with identical properties to WT α 2 δ-1 (15). Surprisingly, we found that the amount of α 2 δ-1-HA detected on the cell surface was strongly reduced by coexpression of Ca V 2.2-BBS, both in the presence and absence of the β subunit ( Fig.…”
Section: Significancementioning
confidence: 73%
“…We therefore examined the cell-surface expression of α 2 δ-1-HA, and the effect of Ca V 2.2 coexpression on this, to gain insight into the interaction site of the auxiliary subunits, with the aim of determining whether they remained associated as judged by colocalization at the cell surface. We used α 2 δ-1-HA for these studies, as we have shown previously that it supports calcium channel currents with identical properties to WT α 2 δ-1 (15). Surprisingly, we found that the amount of α 2 δ-1-HA detected on the cell surface was strongly reduced by coexpression of Ca V 2.2-BBS, both in the presence and absence of the β subunit ( Fig.…”
Section: Significancementioning
confidence: 73%
“…This finding implies that all α 2 δ-1 is proteolytically processed prior to intracellular trafficking into DRG axons. Indeed, our biochemical and cell fractionation data indicate that proteolytic cleavage occurs mainly during trafficking to the plasma membrane (Kadurin et al, 2012) (data not shown). However, this result opens the possibility that uncleaved α 2 δ-1 may reach the cell surface in DRGs cell bodies and have a functional role there.
10.7554/eLife.21143.019Figure 6.Proteolytic processing of endogenous α 2 δ-1 and effect of exogenous expression of α 2 δ-1 and α 2 (3C)δ-1 in DRGs.( a ) DRGs, spinal nerves and dorsal roots from rats, 4 days after SNL, were dissected and segmented according to the diagram.
…”
Section: Resultsmentioning
confidence: 90%
“…We have previously shown that the amount of proteolytically-processed α 2 δ-1 is increased on the cell surface compared to the WCL in transfected tsA-201 cells (Kadurin et al, 2012). However, the present results show that this processing of α 2 δ-1 is not essential for its trafficking to the plasma membrane.…”
Section: Resultsmentioning
confidence: 99%
“…28 It is not clear however, whether similar increases would be evident in neurons that natively express calcium channels with auxiliary subunits. Surprisingly, 29 expression of neither b4 alone nor a 2 d-1 alone increased current density in SCG neurons (Fig. 8).…”
Section: Resultsmentioning
confidence: 99%